2018
DOI: 10.1002/chem.201802647
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Natural Product Rotihibin A as a TOR Kinase Signaling Inhibitor by Unbiased Transcriptional Profiling

Abstract: Bioactive natural products are important starting points for developing chemical tools for biological research. For elucidating their bioactivity profile, biological systems with concise complexity such as cell culture systems are frequently used, whereas unbiased investigations in more complex multicellular systems are only rarely explored. Here, we demonstrate with the natural product Rotihibin A and the plant research model system Arabidopsis thaliana that unbiased transcriptional profiling enables a rapid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…2B ). Previously, Halder et al established a chemical synthesis pathway of rotihibin A and structural analogues ( 26 ). In their structural analogue RotA-D3, the serine residue at position 2 of the amino acid chain was replaced by alanine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2B ). Previously, Halder et al established a chemical synthesis pathway of rotihibin A and structural analogues ( 26 ). In their structural analogue RotA-D3, the serine residue at position 2 of the amino acid chain was replaced by alanine.…”
Section: Resultsmentioning
confidence: 99%
“…In their structural analogue RotA-D3, the serine residue at position 2 of the amino acid chain was replaced by alanine. This derivative turned out to be more active than rotihibin A, as shown by the overall more pronounced plant growth retardation in an A. thaliana bioassay ( 26 ). Interestingly, our data suggest that S. scabies RL-34 would produce a natural rotihibin variant that is modified at the same position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…197 Mechanistic investigations using Arabidopsis thaliana revealed that rotihibin A is an inhibitor of the target of rapamycin (TOR) signaling. 198 Recently, two novel rotihibins C and D, possessing a Thr3 rather than Ser3, were isolated from S. scabies RL-34 and 87-22. These also showed inhibiting activity on plant growth and effects on photosystem II.…”
Section: Reviewmentioning
confidence: 99%